Honduras: two hurricanes, COVID-19, dengue and the need for a new digital health surveillance system. (29th January 2021) - Durón, Reyna M; Sánchez, Eduardo; Choi, Joon Nak; Peralta, Guímel; Ventura, Sandra Gómez; Soto, Ramón J; Rodríguez, Gaspar; Ahrens, Chad; Farach, Efraín; Figueroa, Julio; Pineda, Gracia; Romero, Aldo; et al.
Abstract: A recently published article of this journal stated that informatics solutions can guide better public health decision-making during the COVID 19 (Coronavirus Disease 2019) pandemic. Honduras is a country facing the COVID-19 pandemic with a weak health surveillance system while also fighting a dengue epidemic and the aftermath of two hurricanes that struck its territory in November 2020. In response, we as academics started a COVID-19 and Dengue Observatory combining several technological platforms and developing multidisciplinary research to help the country navigate the crisis. Mapping the pandemic and the natural disasters showed us that technology can be applied toward epidemiology to benefit communities in a time of need by quickly building a basic digital health surveillance system for Honduras.